Exotic animals in the art and culture of the Medici court in Florence - Groom, Angelica, author.
1 online resource.
Keywords: The book examines the roles that rare and exotic animals played in the cultural self-fashioning and the political imaging of the Medici court during the family's reign, first as Dukes of Florence (1532-1569) and subsequently as Grand Dukes of Tuscany (1569-1737). The book opens with an examination of global practices in zoological collecting and cultural uses of animals. The Medici's activities as collectors of exotic species, the menageries they established and their deployment of animals in the ceremonial life of the court and in their art are examined in relation to this wider global perspective. The book seeks to nuance the myth promoted by the Medici themselves that theirs was the most successful princely serraglio in early modern Europe.